Performance evaluation for a unicast Non Delay Tolerant position based routing protocols in VANETs - Abdalla, Ahmed Mohamed (International Journal of Scientific Research and Management (IJSRM), 2017)
Vehicular Ad hoc Networks are special kind of Mobile Ad Hoc Networks. VANET is an emerging technology, which enables an extensive range of applications, including road safety, passenger convenience, self-driven vehicles, and intelligent transportation.Routing in Vehicular Ad hoc Networks is a challenging task due to the unique characteristics of the network. Unicast routing protocols in VANETs are the most fundamental protocols in ad hoc environment and they form the basis for constructing other types of protocols. Unicast routing protocols further classified into topology based, position based, cluster based and hybrid protocols.In this paper protocols belonging to unicast non-delay tolerant position based are discussed. We have implemented our comparison on the NS2 simulator. Simulation of NDT routing protocols A-STAR, CAR, and GyTAR are carried out and the results are presented